Antiproton stopping in H2 and H2O - Bailey, J.; Kadyrov, Alisher; Abdurakhmanov, I.; Fursa, Dmitry; Bray, I. (2015)
©2015 American Physical Society. Stopping powers of antiprotons in H2 and H2O targets are calculated using a semiclassical time-dependent convergent close-coupling method. In our approach the H2 target is treated using a two-center molecular multiconfiguration approximation, which fully accounts for the electron-electron correlation. Double-ionization and dissociative ionization channels are taken into account using an independent-event model. The vibrational excitation and nuclear scattering contributions are also included. The H2O target is treated using a neonization method proposed by C. C. Montanari and J. E. Miraglia [J. Phys. B 47, 015201 (2014)JPAPEH0953-407510.1088/0953-4075/47/1/015201], whereby the ten-electron water molecule is described as a dressed Ne-like atom in a pseudospherical potential. Despite being the most comprehensive approach to date, the results obtained for H2 only qualitatively agree with the available experimental measurements.